Medical aspects of support to children with autism spectrum disorders - Borodina L.G (Moscow State University of Psychology and Education, 2017)
A multiyears experience of medical assistance of children with autism spectrum disorders on the base of the Federal Resource Center for Organization of Comrehencive Support for Children with Autism Spectrum Dizorders is summed up in the article. The forms of psychiatrists' co-work with teachers and psychologists are discussed, as well as the possibilities and effectiveness of farmacological intervention. The compliance questions are raised. A special accent on the importance of psychotherapy for families having children with ASD is made.